PENERAPAN METODE PROFILE MATCHING DALAM PENEMPATAN LOKASI PRAKTIK KERJA LAPANGAN (PKL) MAHASISWA BERBASIS WEB - Honainah Honainah; Siti Romelah; Anis Yusrotun Nadhiroh (Universitas Islam Madura, 2020)
Practical Work is a mandatory activity for all students of the Engineering Study Program at Nurul Jadid University with a time span of one to two months. In determining the location of PKL (Practical Work ), a problem that often occurs is the competencies incompatibility in the students placement based on the need of the company where the Practical Work is going to take place. The purpose of this research is to produce a decision support system design in Placement of Practical Work for students of Faculty of Engineering, Nurul Jadid University. The data processed in this study are student data, value data, and several other supporting data. Furthermore, the data from the students are processed using the Profile Matching method. The processing stage is to matching the value of the weight of each criterion with the value of each student. Later, it will determine the core and second factor. The results of testing this method are to produce recommendations in the form of ranking each student and provide the best alternative solutions in determining the placement of practical work for students of the Faculty of Engineering, Nurul Jadid University.